Enterprise Architecture Planning Design Using Zachman Framework on TIX.ID Application - Nurul Fadilah Aswar; Andi Rifqah Purnama Alam; Andika Isma; Maulana Rumi Irwan Balo (Indonesian Journal of Enterprise Architecture, 2023)
The process of implementing the Zachman framework in a company is a strategy for developing and managing the company. Start-up companies like TIX.ID also apply this strategy to analyze and organize. The process of identifying using the zachman framework implementation in the application company TIX.ID, which is a service company, provides a real space for companies to be able to assess the right strategy for developing corporate architecture related to important matters concerning the running of the company. This implementation makes it easy for companies to make the right utilization of resources and decision-making processes for efficiency and effectiveness in the digital services industry. Not only for companies, the benefits of implementing the Zachman framework can be felt directly by users who feel the success of the application in providing comfort for the services provided.